Prospective evaluation of MRI compared with CT for the etiology of abdominal pain in emergency department patients with concern for appendicitis. Issue 5 (20th March 2019) - Harringa, John B.; Bracken, Rebecca L.; Davis, John C.; Mao, Lu; Kitchin, Douglas R.; Robbins, Jessica B.; Ziemlewicz, Timothy J.; Pickhardt, Perry J.; Reeder, Scott B.; Repplinger, Michael D.
Abstract : Background: Computed tomography (CT) is commonly used in the Emergency Department (ED) to evaluate patients with abdominal pain, but exposes them to ionizing radiation, a possible carcinogen. MRI does not utilize ionizing radiation and may be an alternative. Purpose: To compare the sensitivity of MRI and CT for acute abdominopelvic ED diagnoses. Study Type: Prospective, observational cohort. Population: ED patients ≥12 years old and undergoing CT for possible appendicitis. Field Strength/Sequence: 1.5 T MRI, including T1 ‐weighted, T2 ‐weighted, and diffusion‐weighted imaging sequences. Assessment: Three radiologists independently interpreted each MRI and CT image set separately and blindly, using a standard case report form. Assessments included likelihood of appendicitis, presence of an alternative diagnosis, and likelihood that the alternative diagnosis was causing the patient's symptoms. An expert panel utilized chart review and follow‐up phone interviews to determine all final diagnoses. Times to complete image acquisition and image interpretation were also calculated. Statistical Tests: Sensitivity was calculated for each radiologist and by consensus (≥2 radiologists in agreement) and are reported as point estimates with 95% confidence intervals. Two‐sided hypothesis tests comparing the sensitivities of the three image types were conducted using Pearson's chi‐squared test with the traditional significance level of P = 0.05. Results: There were 15 different acute diagnoses identified on the CT/MR images of 113 patients. Using individual radiologist interpretations, the sensitivities of noncontrast‐enhanced MRI (NCE‐MR), contrast‐enhanced MR (CE‐MR), and CT for any acute diagnosis were 77.0% (72.6–81.4%), 84.2% (80.4–88.0%), and 88.7% (85.5–92.1%). Sensitivity of consensus reads was 82.0% (74.9–88.9%), 87.1% (81.0–93.2%), 92.2% (87.3–97.1%), respectively. There was no difference in sensitivities between CE‐MR and CT by individual ( P = 0.096) or consensus interpretations ( P = 0.281), although NCE‐MR was inferior to CT in both modes of analysis ( P < 0.001, P = 0.031, respectively). Data Conclusion: The sensitivity of CE‐MR was similar to CT when diagnosing acute, nontraumatic abdominopelvic pathology in our cohort. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1651–1658.